Linguagem gauchesca: história, memória e tradição no Rio Grande do Sul - Tatsch, Juliane (2017)
This thesis is about the constitution of a gauchesque language based on the semantic functioning of the word tradition present in texts that constitute discourses about the gaucho and that integrate a set of materialities produced in gauchesca language, constituted and represented in different textualities of the advertising discourse, for to demonstrate how this language is constituted, sustained and maintained by tradition, and how this same tradition, which is recurrent in the discourse on the social type of Gaucho, determines the gauchesque language. We seek, from the theoretical perspective of Semantics of the Event, by the linguist Eduardo Guimarães (2002), to analyze the functioning of language in the event of enunciation. Thus, language is thought of in its functioning, so it is an already-said that repeats itself, but which is articulated to other sayings, other utterances. The word tradition is itself an event because it carries the story and means according to the place of the saying. For this, we consider the designation of the word tradition, that is, the relation of this word to others in the statement that leads to the production of other senses. These statements marked linguistically as the gaucho are configured as a discourse on the gaucho, which affirms a regional identity, which authorizes the gaucho to be inserted in a national culture. This speech is enunciated both in the language and in the language, and it is a saying about the gaucho that is a gauchesque language. The analysis of the semantic functioning of the designations on which the Semantic Domain of Determination of the word tradition was analyzed, explained through the procedures of articulation and rewriting, how the word tradition articulates and rewrites establishing different relations with other words and with other utterances, in order to understand what it designates and what meanings it mobilizes in the set of studied texts. Within this theoretical-methodological framework, the analytic categories reveal the semantic functioning of the word tradition through the rewriting and articulation procedures, which characterize, as indicated by Guimarães (2005), different modes of occurrence of semantic functions. The statements observed in the enunciative sequences constitute a space of enunciation in which the signification is produced by the constitution of discourses on and in the gauchesque language, producing a specification that determines this language. Therefore, gauchesque language means by what it designates. A particular and regional meaning that provides the production of a knowledge about the regional language endorsed by the gathering of a set of textualities that constitute sayings about the gaucho that update the discursive memory and construct a way of knowing about the language spoken by the gaucho subject. That is why we say that the functioning of the word tradition within gauchesque language is not static, homogeneous, with definitive meanings. The Gaucho language when it works is an event that puts this gaucho subject in evidence. It is a way of saying (say in and saying about) what the gaucho means and is constitutive of this subject in his social relations. Therefore, because of its specificity and particularity, gauchesque language is a way of approaching the gaucho subject with tradition.